Paneth cell ontogeny in term and preterm ovine models - Bautista, Geoanna M.; Cera, Anjali J.; Schoenauer, Rebecca J.; Persiani, Michele; Lakshminrusimha, Satyan; Chandrasekharan, Praveen; Gugino, Sylvia F; Underwood, Mark A.; McElroy, Steven J. (Frontiers in Veterinary Science, 2024)
Paneth cells are critically important to intestinal health, including protecting intestinal stem cells, shaping the intestinal microbiome, and regulating host immunity. Paneth cell biology in the immature intestine is often modeled in rodents with little information in larger mammals such as sheep. Previous studies have only established the distribution pattern of Paneth cells in healthy adult sheep. Our study aimed to examine the ontogeny, quantification, and localization of Paneth cells in fetal and newborn lambs at different gestational ages and with perinatal transient asphyxia. We hypothesized that ovine Paneth cell distribution at birth resembles the pattern seen in humans (highest concentrations in the ileum) and that ovine Paneth cell density is gestation-dependent. Intestinal samples were obtained from 126-127 (preterm, with and without perinatal transient asphyxia) and 140-141 (term) days gestation sheep. Samples were quantified per crypt in at least 100 crypts per animal and confirmed as Paneth cells through immunohistochemistry. Paneth cells had significantly higher density in the ileum compared to the jejunum and were absent in the colon. Exposure to perinatal transient asphyxia acutely decreased Paneth cell numbers. These novel data support the possibility of utilizing ovine models for understanding Paneth cell biology in the fetus and neonate.